Preparation of fish decalcified bone matrix and its bone repair effect in rats - Liu, Zichao; Jiang, Xiaorui; Wang, Kai; Zhou, Yongshun; Li, Tingting; Gao, Jianfeng; Wang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Decalcified bone matrix (DBM) has great potential and application prospects in the repair of bone defects due to its good biocompatibility and osteogenic activity. In order to verify whether fish decalcified bone matrix (FDBM) has similar structure and efficacy, this study used the principle of HCl decalcification to prepare the FDBM by using fresh halibut bone as the raw material, and then degreasing, decalcifying, dehydrating and freeze-drying it. Its physicochemical properties were analyzed by scanning electron microscopy and other methods, and then its biocompatibility was tested by in vitro and in vivo experiments. At the same time, an animal model of femoral defect in rats was established, and commercially available bovine decalcified bone matrix (BDBM) was used as the control group, and the area of femoral defect in rats was filled with the two materials respectively. The changes in the implant material and the repair of the defect area were observed by various aspects such as imaging and histology, and its osteoinductive repair capacity and degradation properties were studied. The experiments showed that the FDBM is a form of biomaterial with high bone repair capacity and lower economic cost than other related materials such as BDBM. FDBM is simpler to extract and the raw materials are more abundant, which can greatly improve the utilization of marine resources. Our results show that FDBM not only has a good repair effect on bone defects, but also has good physicochemical properties, biosafety and cell adhesion, and is a promising medical biomaterial for the treatment of bone defects, which can basically meet the clinical requirements for bone tissue repair engineering materials.